The Mediating Role of School Culture in the Influence of Clinical Supervision on MTs Teachers in Situbondo Regency, East Java, Indonesia - Musyaffa Rafiqie; Erfan Habibi; Suyitno Suyitno; Mohamad Aso Samsudin (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2025)
Purpose of the StudyThis study aims to investigate and analyze the mediating role of school culture in the influence of clinical supervision on teachers’ pedagogical competence at Islamic Junior High Schools (MTs) in Situbondo Regency, East Java, Indonesia. Employing a quantitative approach with an explanatory research design, the study uses a survey method to address the research problem and objectives. The questionnaire was constructed based on the main variables: school culture, clinical supervision, and teachers’ pedagogical competence. Data were collected from a sample of 100 teachers selected through random sampling from MTs across Situbondo Regency. The data analysis was conducted using the Partial Least Squares (PLS) method with SmartPLS software. The results of the hypothesis testing show that clinical supervision has a significant positive effect on teachers’ pedagogical competence, indicating that higher levels of supervision lead to greater pedagogical capabilities. Clinical supervision also significantly affects school culture, suggesting that more effective supervision enhances the overall school culture. Moreover, school culture itself significantly influences teachers’ pedagogical competence, meaning that a strong school culture contributes to better teaching practices. Additionally, school culture mediates the relationship between clinical supervision and pedagogical competence, indicating that clinical supervision indirectly improves pedagogical competence through its impact on school culture. These findings highlight the important roles of both clinical supervision and school culture in enhancing teachers’ pedagogical competence, with school culture serving as a critical mediating factor.